Manga the Citi exhibition - Matsuba, Ryoko; Rousmaniere, Nicole Coolidge 1961- (Thames & Hudson, 2019)
Translated literally as 'pictures run riot', manga refers to a form of Japanese narrative art that has grown over the centuries to become a global phenomenon. Initially referring to graphic prints, novels and comics, manga has expanded beyond its original forms to include animation, art, fashion and new media such as film and gaming, and has international reach. Immensely popular with people of all ages, manga is big business, with a turnover of GBP 3 billion in Japan in 2016. Arranged into six broadly chronological, thematic chapters, this book traces the origins of manga, from its beginnings to the present day. Each section opens with an essay, followed by interviews, features and manga selections. The first chapter focuses on understanding manga through reading, drawing and producing. The second explores the power of storytelling, examining manga's presentation of reality through printed formats and subject matter. The third chapter centres on the power of the seen and the unseen worlds. Chapter four shifts the attention from the art form directly to its role in society, starting with manga's grass roots and moving on to fandom, education and the future of manga in an uncertain world. The penultimate chapter highlights the works of sixteen select manga artists, forming a visual timeline of seminal works. The final chapter examines manga's expanding boundaries, including the avant-garde, media crossover and manga's growing international reach and influence. 0ffering a revealing insight into the world of manga, this book will appeal to manga fans and to all those interested in graphic art, in all its forms. Exhibition: British Museum, London, UK (23.05.-26.08.2019).